Identification of novel long non-coding RNA involved in Sertoli cell of non-obstructive azoospermia based on microarray and bioinformatics analysis - Karoii, Danial Hashemi; Abroudi, Ali Shakeri; Darvar, Maryam; Djamali, Melika; Azizi, Hossein; Skutella, Thomas (Genomics, 2025)
Non-obstructive azoospermia (NOA) is a severe form of male infertility, yet its underlying molecular mechanisms remain poorly understood. This study aimed to identify key regulatory non-coding RNAs (ncRNAs) and hub genes associated with NOA through an integrative bioinformatics approach. Using microarray analysis, we examined 4956 ncRNAs and identified 29 differentially expressed ncRNAs (14 upregulated, 15 downregulated) in NOA compared to healthy individuals. Co-expression analysis revealed significant interactions between lncRNAs, miRNAs, and mRNAs, predicting 31 target mRNAs within the regulatory network. Further, single-cell transcriptomic analysis identified four pivotal hub genes in NOA Sertoli cells: CLTC, XIAP, and DHFR (upregulated) and STMN1 (downregulated). Functional enrichment analysis highlighted critical pathways, including mitotic spindle organization and phosphatase activity, suggesting their involvement in NOA pathophysiology. Our findings provide novel insights into the molecular mechanisms underlying NOA and propose potential biomarkers for improved diagnosis and therapeutic strategies.